(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
The Earth Charter is, for several reasons, a radical document. First, the Earth Charter is a people’s document intentionally created outside the usual context for international agreements and, initially, not formally adopted by the United Nations General Assembly. It proposes solutions that are transnational and that address people and their personal interactions with their environment rather than setting an agenda for political bodies, national or international. Thus the Earth Charter is non-formal in its mode of creation and readily accessible to the public. Its consensual nature allows it to have a broad appeal, and its publication represents an alternative to conventional ways of producing such international documents. In short, there is an intent in this process to do things differently. Some words from the brief history of the document (History of the Earth Charter) make this clear.